A linguagem visual do livro didático de educação a distância - Pacheco, Leonardo Paiva de Almeida (2018)
The objective of this research was to analyze the visual language applied to didactic books aimed at distance education (EAD) with the purpose of guiding Public Education Institutions (IPE) regarding the preparation and choice of the book that is visually more appropriate. In order to achieve this, a documentary research was carried out, whose cut was the first years books (because they were the first contact of the student with the visual language used in this material) of the graduation course in Visual Arts EAD of the Federal University of Espírito Santo (Ufes ). The choice for the distance modality course was because in that modality the book can interfere in the teaching-learning process in a more incisive way than in face-to-face teaching. The research had as theoretical framework authors of graphic design that are based on Gestalt Theory, as Donis A. Dondis (2007) and Professor João Gomes Filho (2008). The methodology was an adaptation of John C. Flanagam's "Critical Incident Technique" (1954) associated with the "visual form reading system" of Gomes Filho (2008). The visual compositions were analyzed in order to identify the characteristics that favor and those that compromise the visual communication of the didactic book: clarity, emphasis, contrast and repetition were the most relevant visual techniques and those that gave the highest “índice de pregnância” to the compositions. The major compositional problems encountered were lack of alignment of the elements, poor use of compositional space and visual pollution due to excessive emphasis. The work is included in the field of research Operations Management in the Public Sector of the Master in Public Management because of the investment of public resources destined to the production of didactic book